The Role of Magnesium in the Management of Cerebral Vasospasm - Mitchell J. Odom (Neurology Research International, 2013)
Subarachnoid hemorrhage (SAH) is characterized by bleeding into the subarachnoid space, often caused by ruptured aneurysm. Aneurysmal rupture occurs in 700,000 individuals per year worldwide, with 40,000 cases taking place in the United States. Beyond the high mortality associated with SAH alone, morbidity and mortality are further increased with the occurrence of cerebral vasospasm, a pathologic constriction of blood vessels that can lead to delayed ischemic neurologic deficits (DIND). Treatment of cerebral vasospasm is a source of contention. One extensively studied therapy is Magnesium (Mg) as both a competitive antagonist of calcium at the N-methyl D-aspartate (NMDA) receptor, and a noncompetitive antagonist of both IP3 and voltage-gated calcium channels, leading to smooth muscle relaxation. In our literature review, several animal and human studies are summarized in addition to two Phase III trials assessing the use of intravenous Mg in the treatment of SAH (IMASH and MASH-2). Though many studies have shown promise for the use of Mg in SAH, there has been inconsistency in study design and outcomes. Furthermore, the results of the recently completed clinical trials have shown no significant benefit from using intravenous Mg as adjuvant therapy in the treatment of cerebral vasospasm.